Pencarian attechment baru setelah kehilangan figur penting: studi kasus kebutuhan kasih sayang pada dewasa muda - Najwa, Aina (Maliki Interdisciplinary Journal, 2026)
The loss of important attachment figures such as parents during young adulthood causes complex and profound psychological impacts. This study aims to analyze the dynamics of searching for new attachments as a coping strategy after the loss of important figures in young adulthood. A literature review method was used by analyzing journal articles, books, and academic publications from electronic databases such as Google Scholar, PubMed, and ScienceDirect with publication criteria from the last 10 years. The results of the review indicate that attachment patterns formed since childhood influence how individuals respond to loss and seek new emotional connections. Individuals with secure attachment tend to form adaptive relationships, whereas individuals with insecure attachment are vulnerable to maladaptive relationship patterns such as rebound relationships and excessive dependency. Unresolved grieving processes can develop into complicated grief that hinders the developmental task of intimacy versus isolation in the young adulthood phase. Healthy searching for new attachments requires a balance between processing loss and building a new life, with social support and professional interventions that are sensitive to individual and cultural contexts. The concept of continuing bonds shows that individuals can maintain emotional connections with deceased figures while forming new meaningful attachments.